Insulin-Independent and Dependent Glucose Transporters in Brain Mural Cells in CADASIL - Panahi, Mahmod; Rodriguez, Patricia Rodriguez; Fereshtehnejad, Seyed-Mohammad; Arafa, Donia; Bogdanovic, Nenad; Winblad, Bengt; Cedazo-Minguez, Angel; Rinne, Juha; Darreh-Shori, Taher; Hase, Yoshiki; Kalaria, Raj N.; Viitanen, Matti; et al. (Frontiers in Genetics, 2020)
Typical cerebral autosomal-dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) is caused by mutations in the human NOTCH3 gene. CADASIL is characterised by subcortical ischemic strokes due to severe arteriopathy and fibrotic thickening of small vessels. Blood regulating vascular smooth muscle cells (VSMCs) appear as the key target in CADASIL but the pathogenic mechanisms remain unclear. With the hypothesis that glucose metabolism is disrupted in VSMCs in CADASIL, we investigated postmortem tissues and VSMCs derived from CADASIL patients to explore gene expression and protein immunoreactivity of glucose transporters (GLUTs), particularly GLUT4 and GLUT2 using quantitative RT-PCR and immunohistochemical techniques. In vitro cell model analysis indicated that both GLUT4 and -2 gene expression levels were down-regulated in VSMCs derived from CADASIL patients, compared to controls. In vitro studies further indicated that the down regulation of GLUT4 coincided with impaired glucose uptake ability in VSMCs, which could be partially rescued by insulin treatment. Our observations on reduction in glucose transporters in VSMCs are consistent with previous findings of decreased cerebral blood flow and glucose uptake in CADASIL patients. The impaired ability of glucose uptake is rescue by insulin is also consistent with previously reported lower proliferation rates of VSMCs derived from CADASIL subjects. Overall, these observations are consistent with the development of severe arteriopathy in CADASIL, in which VSMCs are replaced by widespread fibrosis.